Dle-Wdm: Metaheuristic to Routing and Wavelength Assignment in Dynamic Traffic [Edrl-Mdl: Metaheurística Para el Enrutamiento y Asignación de Longitud de Onda en Tráfico Dinámico] - Travieso-Torres, J; Rodriguez-Garcia, A; Rodriguez-Garcia, A (Universidad de Tarapaca, 2017)
The heuristics used to solve the problem of routing and wavelength assignment in optical networks in dynamic scenarios had been partially successful and especially do not respond well when subjected to estrés. This article describes a new strategy called Snake-Two that uses the algorithm Snake-One with the monitoring of network links, trying to concentrate on the most used traffic areas leaving more openings in the rest of the network is proposed, which allows decreasinge the likelihood of blocking incoming network requests. The results improve the average probability of blocking up to 37.7% of the highest obtained results. However, the use of the network continues to increase. These results ensure that the improved care of requests for lower scenarios to 140 Erlangs. © 2017, Universidad de Tarapaca. All rights reserved.